Assessment of the Knowledge of Biosafety Amongst Medical Laboratory Personnel: A Case Study of Federal Medical Centre, Katsina Nigeria - Anas Babangida Aliyu Bala Hauwa Bako Mujahid Abdullahi Ahmad Mohammad Bello Mahmud Inusa Yandutse (Sokoto Journal of Medical Laboratory Science)
Open PDF